Profiling of Cxcl12 Receptors, Cxcr4 and Cxcr7 in Murine Testis Development and a Spermatogenic Depletion Model Indicates a Role for Cxcr7 in Controlling Cxcl12 Activity - Westernströer, Birgit; Terwort, Nicole; Ehmcke, Jens; Wistuba, Joachim; Schlatt, Stefan; Neuhaus, Nina (PLOS ONE, 2014)
In mice the chemokine Cxcl12 and its receptor Cxcr4 participate in maintenance of the spermatogonial population during postnatal development. More complexity arises since Cxcl12 also binds to the non-classical/atypical chemokine receptor Cxcr7. We explored the expression pattern of Cxcl12, Cxcr4 and Cxcr7 during postnatal development in mouse testes and investigated the response of Cxcl12, Cxcr4, Cxcr7 and SSC-niche associated factors to busulfan-induced germ cell depletion and subsequent recovery by RNA expression analysis and localization of the proteins. In neonatal testes transcript levels of Cxcl12, Cxcr4 and Cxcr7 were relatively low and protein expression of Cxcr7 was restricted to gonocytes and spermatogonia. During development, RNA expression of Cxcl12 remained stable but that of Cxcr4 and Cxcr7 increased. Cxcr7 was expressed in germ cells located at the basement membrane of the seminiferous tubules. In adult testes, transcript levels of Cxcl12 were highest while the localization of Cxcr7 did not change. Following germ cell depletion, a significantly increased expression of Cxcl12 and a decreased expression of Cxcr7 were observed. Germ cells repopulating the seminiferous tubules were immunopositive for Cxcr7. We conclude that Cxcr7 expression to be restricted to premeiotic germ cells throughout postnatal testicular development and during testicular recovery. Hence, the spermatogonial population may not only be simply controlled by interaction of Cxcl12 with Cxcr4 but may also involve Cxcr7 as an important player.